2015
DOI: 10.1891/1052-3073.26.1.79
|View full text |Cite
|
Sign up to set email alerts
|

Homeownership and Financial Strain Following the Collapse of the Housing Market: A Comparative Study on Loan Delinquencies Between Black and White Households

Abstract: The objectives of this study were to evaluate the extent to which homeownership contributed to household financial strain as measured by loan delinquency after the onset of the recent housing market crash, and to examine if the impact of homeownership on household financial strain differed for Black and White households. Using data from the 2010 Survey of Consumer Finances, we found that, after controlling for other factors, a household's housing preferences had a potential effect on the likelihood of experien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
3
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 22 publications
2
3
0
Order By: Relevance
“…Only subjective financial literacy is negatively associated with debt delinquency, while objective financial literacy shows no difference in all three measures of financial burdens, suggesting that financial knowledge may have a limited role in predicting financial burdens. This study shows that overspending, an indication of present bias, is positively associated with, and a longer financial planning horizon, an indication of future orientation, is negatively associated with debt delinquency and insolvency, consistent with results from previous empirical research on debt delinquency (Bieker and Yuh, 2015) and predictions based on consumer behavioral biases (Zinman, 2014). These findings suggest that consumer behavioral bias may play an important role in consumer borrowing decisions.…”
Section: Discussionsupporting
confidence: 89%
See 3 more Smart Citations
“…Only subjective financial literacy is negatively associated with debt delinquency, while objective financial literacy shows no difference in all three measures of financial burdens, suggesting that financial knowledge may have a limited role in predicting financial burdens. This study shows that overspending, an indication of present bias, is positively associated with, and a longer financial planning horizon, an indication of future orientation, is negatively associated with debt delinquency and insolvency, consistent with results from previous empirical research on debt delinquency (Bieker and Yuh, 2015) and predictions based on consumer behavioral biases (Zinman, 2014). These findings suggest that consumer behavioral bias may play an important role in consumer borrowing decisions.…”
Section: Discussionsupporting
confidence: 89%
“…For each column, the portfolios are presented in the order of their risky scores estimated in Table 4, in which #1 means the riskiest debt portfolio for the indicator in that column. For example, the portfolio type, 124 (mortgage-other-vehicle debts) has the largest probability, compared to other portfolio types, to be associated with debt pressure, given control variables an indication of present bias, is positively associated with, and a longer financial planning horizon, an indication of future orientation, is negatively associated with debt delinquency and insolvency, consistent with results from previous empirical research on debt delinquency (Bieker and Yuh, 2015) and predictions based on consumer behavioral biases (Zinman, 2014). These findings suggest that consumer behavioral bias may play an important role in consumer borrowing decisions.…”
Section: Discussionsupporting
confidence: 85%
See 2 more Smart Citations
“…Baum and O'Malley (2003) found that 45% of undergraduate borrowers and 54% of graduate school borrowers in the United States had debt-to-income ratios in excess of 8%. While previous studies have focused on a debt-to-income ratio that targets the household level (Bieker & Yuh, 2015;Sherraden & McBride, 2010), this study found that only limited research had specifically addressed the student loan payment-to-income ratio.…”
Section: Determinants Of Student Loansmentioning
confidence: 91%